2001
DOI: 10.1074/jbc.m004430200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Properties of Zic Proteins as Transcriptional Regulators and Their Relationship to GLI Proteins

Abstract: Zic family genes encode zinc finger proteins, which play important roles in vertebrate development. The zinc finger domains are highly conserved between Zic proteins and show a notable homology to those of Gli family proteins. In this study, we investigated the functional properties of Zic proteins and their relationship to the GLI proteins. We first established an optimal binding sequence for Zic1, Zic2, and Zic3 proteins by electrophoretic mobility shift assay-based target selection and mutational analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 45 publications
4
144
1
1
Order By: Relevance
“…The formation of Zic-Gli heterodimers is likely to preclude an interaction with DNA, as zinc fingers 3-5 in both proteins are thought to be important for DNA recognition (Pavletich and Pabo, 1993;Mizugishi et al, 2004). Accordingly, Zic proteins are reported to inhibit transcriptional activation by Gli and vice versa in Xenopus embryos and in cell culturebased reporter assays (Brewster et al, 1998;Koyabu et al, 2001;Mizugishi et al, 2001). Thus, specific interaction between Zic and Gli proteins is an attractive mechanism for regulating their respective activities in cells where they are co-expressed.…”
Section: Interacting Proteinsmentioning
confidence: 99%
“…The formation of Zic-Gli heterodimers is likely to preclude an interaction with DNA, as zinc fingers 3-5 in both proteins are thought to be important for DNA recognition (Pavletich and Pabo, 1993;Mizugishi et al, 2004). Accordingly, Zic proteins are reported to inhibit transcriptional activation by Gli and vice versa in Xenopus embryos and in cell culturebased reporter assays (Brewster et al, 1998;Koyabu et al, 2001;Mizugishi et al, 2001). Thus, specific interaction between Zic and Gli proteins is an attractive mechanism for regulating their respective activities in cells where they are co-expressed.…”
Section: Interacting Proteinsmentioning
confidence: 99%
“…The lhh reporter plasmid (TK-6GBS-Luc) expressed luciferase under control of the thymidine kinase (TK) promoter and was a gift of Dr. Jun Aruga (Developmental Neurobiology Laboratory, Brain Science Institute, RIKEN, Japan) [39]. The plasmid contained six tandem copies of the GL1-target site, 5Ј-TGGGTGGTC-3Ј, inserted upstream of the TK promoter.…”
Section: Expression and Activity Of Ihh-n Protein By Adv-mediated Ihhmentioning
confidence: 99%
“…ZFDs have been implicated in many functions, including DNA recognition, protein/protein interactions, transcriptional repression, and nuclear localization (52)(53)(54)(55)(56). Examination of the secondary structure of the Glis1 zinc finger domain indicated that the second half of each zinc finger consists of an ␣-helix.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear localization of Gli proteins was regulated at multiple levels that involves Sonic hedgehog signaling, nuclear import and export signals, and interactions with Fused (FU) and Suppressor of Fused (SUFUH) (60 -62). In addition, the nuclear localization of Gli proteins can be facilitated through heterodimerization with Zic proteins (56). Future studies have to ascertain the precise mechanisms that determine the nuclear transport of Glis1.…”
Section: Discussionmentioning
confidence: 99%